2016
DOI: 10.1007/s13277-016-5089-8
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic increase in efficacy of a combination of 2-deoxy-d-glucose and cisplatin in normoxia and hypoxia: switch from autophagy to apoptosis

Abstract: Resistance to drugs, which is aggravated by hypoxia, is a well-known feature of tumors. The combination of drug exposure and hypoxia can give rise to several survival strategies in the exposed cells. Glioblastoma multiforme (GBM) is among the most hypoxic of solid tumors, and we have used glial cells to identify a drug combination that would be synergistically effective in these cells under both normoxia and hypoxia. Cisplatin (CP) and 2-deoxy-D-glucose (2-DG), which have been used for second-line therapy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…More and more studies reported that increased aerobic glycolysis is a hallmark of cancer and plays a role in chemoresistance in different cancer cells [ 7 9 , 22 , 23 ]. To directly demonstrate if 2-DG treatment can reverse GC resistance, we incubated ALL and Raji cells with 1 mM 2-DG and/or 1 μM dexamethasone (Dex) for 24 h and 48 h. 2-DG combined with Dex inhibited the viability of GC resistant cells (Raji, Jurkat, CEM-C1-15, Molt-4) synergistically (Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…More and more studies reported that increased aerobic glycolysis is a hallmark of cancer and plays a role in chemoresistance in different cancer cells [ 7 9 , 22 , 23 ]. To directly demonstrate if 2-DG treatment can reverse GC resistance, we incubated ALL and Raji cells with 1 mM 2-DG and/or 1 μM dexamethasone (Dex) for 24 h and 48 h. 2-DG combined with Dex inhibited the viability of GC resistant cells (Raji, Jurkat, CEM-C1-15, Molt-4) synergistically (Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…As suggested, methenamine has been successfully applied to treat central nervous system infections in the past, suggesting that it crosses through the blood–brain barrier and releases cytocidal levels formaldehyde in hypoxic tissues. In tumours, hypoxia aggravates chemotherapy and radiotherapy resistance, and glioblastomas are among the most hypoxic of solid tumours . Hypoxic cell clones do not actively divide due to lack of sufficient cellular energy and non‐dividing cells are more resistant to chemo‐radiotherapy as their DNA is more compacted and shielded with histone and non‐histone proteins.…”
Section: Rationale For Employing Methenamine To Treat and Chemo‐radiomentioning
confidence: 99%
“…In tumours, hypoxia aggravates chemotherapy and radiotherapy resistance, and glioblastomas are among the most hypoxic of solid tumours. 25 Hypoxic cell clones do not actively divide due to lack of sufficient cellular energy and non-dividing cells are more resistant to chemo-radiotherapy as their DNA is more compacted and shielded with histone and non-histone proteins. Moreover, hypoxia activates purinergic signalling allowing multi-drug resistance in glioblastoma.…”
Section: R Ationale For Employing Me Thenamine To Tre At and Chemo mentioning
confidence: 99%
“…We have earlier shown the synergistic effect of 2-deoxy-D-glucose and cisplatin on cell monolayers under both hypoxia and normoxia. However this involved a distinct mechanism of conversion of autophagy to apoptosis, and also the effect on cancer stem cells was not demonstrated [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…NS-398 was taken as the prototype COX-2 inhibitor which was used in combination with the drugs (BCNU, Temozolomide (TMZ), Cisplatin (CP) and 2-Deoxy-D- glucose (2-DG)). While TMZ and BCNU are being used in glioma [ 40 – 42 ], CP and 2-DG have been tried earlier [ 6 , 43 46 ]. We observed synergism under both hypoxia and normoxia, only with the combination of NS-398 and BCNU.…”
Section: Introductionmentioning
confidence: 99%